THE EFFECTIVENESS OF SIMON SAYS GAME TO IMPROVE STUDENTS VOCABULARY MASTERY IN LEARNING ENGLISH - Suci Humairoh; Absharini Kardena; Rahmi Novianti (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This research was conducted based on the problems found in the learning process about vocabulary. To understand language well, speak better, or good writing requires a good vocabulary to be successful in any of these areas. Teachers must be good at choosing methods or techniques in learning to be used in teaching, not all methods or techniques can be used, because learning methods are real forms in the form of steps for implementing a lesson in order to achieve learning goals. In this research to teach vocabulary, the researcher choose to use a game. Game is an activity that can help the process of learning and creating students are more active in learning because they feel happy and relaxed in learning. The purpose of this research is to find out whether the Simon Says game is effective or not for use in learning, especially vocabulary. Because what we are going to examine now is the effectiveness of the Simon Says game in increasing student vocabulary. The method used in this research is descriptive qualitative research. Which aims to describe or give an idea of how effective the Simon Says game is for students vocabulary in learning process. The researcher gave vocabulary from descriptive text material and asked students to memorize it. Then the vocabulary will be played in the Simon Says game. The results of this study indicate that the Simon Says game is very effective for teaching vocabulary. Because judging from the many changes after several meetings with students and playing this Simon Says game for learning.